Areas Of Application Of Automated Electric Drives In Robototechnics - Khusan Rakhmonov (Zien Journals, 2025)
In this article we will consider the application of automated electric drives of robotics andtechnical complexes and a number of production processes using industrial robots.
Keywords: robotics; industrial robots; stamping; manipulators